2010
DOI: 10.1111/j.1365-2966.2010.16726.x
|View full text |Cite
|
Sign up to set email alerts
|

Radio observations of NGC 6388: an upper limit on the mass of its central black hole

Abstract: We present the results of deep radio observations with the Australia Telescope Compact Array (ATCA) of the globular cluster NGC 6388. We show that there is no radio source detected (with an rms noise level of 27 μJy) at the cluster centre of gravity or at the locations of any of the Chandra X‐ray sources in the cluster. Based on the fundamental plane of accreting black holes which is a relationship between X‐ray luminosity, radio luminosity and black hole mass, we place an upper limit of ∼1500 M on the mass of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
2

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 53 publications
1
41
2
Order By: Relevance
“…and averaged quiescent luminosities of L X 10 32 −10 33 erg/s. The relatively small uncertainty in the position of IGR J17361-4441, as determined thanks to the Chandra observation of the source carried out by Pooley et al (2011), suggests that the newly discovered INTEGRAL transient is associated with neither the objects detected previously in quiescence by Cseh et al (2010), nor the COG of NGC 6388 (see Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…and averaged quiescent luminosities of L X 10 32 −10 33 erg/s. The relatively small uncertainty in the position of IGR J17361-4441, as determined thanks to the Chandra observation of the source carried out by Pooley et al (2011), suggests that the newly discovered INTEGRAL transient is associated with neither the objects detected previously in quiescence by Cseh et al (2010), nor the COG of NGC 6388 (see Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
“…To date, the deepest X-ray observations of the GC were carried out with Chandra and reported by Cseh et al (2010). These authors found a number of sources located close to the core of the GC (sources #3, #7, and #12), with spectral properties similar to those of the X-ray binaries 4 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This issue was considered by several authors. For example, Grindlay et al (2001) provided the census of the compact objects and binary populations in the globular cluster 47 Tuc and obtained an upper limit to the central IMBH of a few hundred solar masses; Nucita et al (2008) showed that the core of the globular cluster NGC 6388 harbors several X-ray sources; and Cseh et al (2010) refined the analysis putting an upper limit to the central IMBH mass of a few thousand solar masses (see also Bozzo et al 2011;Nucita et al 2012).…”
Section: An Intermediate-mass Black Hole In the Fornax Galaxy: High-ementioning
confidence: 99%